2009
DOI: 10.1111/j.1540-8175.2008.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Estimation of Pulmonary Vascular Resistance in Pulmonary Hypertension

Abstract: Background: Determination of pulmonary vascular resistance (PVR) in patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 16 publications
(18 reference statements)
9
89
5
1
Order By: Relevance
“…As previously described, all the equations became less accurate when the PVR increased. 33, 34 Our results confirmed than estimation of PVR is not adequately established with ECHO. 23 When this value is important to guide therapy, the calculation must be determined using RHC.…”
Section: Doutreleau S Et Alsupporting
confidence: 78%
“…As previously described, all the equations became less accurate when the PVR increased. 33, 34 Our results confirmed than estimation of PVR is not adequately established with ECHO. 23 When this value is important to guide therapy, the calculation must be determined using RHC.…”
Section: Doutreleau S Et Alsupporting
confidence: 78%
“…[33][34][35][36] These indirect measures have not been validated with sufficient patient numbers, and questions about accuracy persist. Consequently, catheterization-derived measurement of PVR is still required.…”
Section: Estimates Of Pap and Pvrmentioning
confidence: 99%
“…However, when the Abbas formula was applied to patients with a PVR >8 Wood units, the relationship was no longer significant. 40 Recently, Opotowsky et al 41 showed a very strong correlation between invasively measured PVR and estimated PVR using a model based on the ratio of Doppler-estimated systolic PAP to RVOT velocity time integral and the presence of RVOT Doppler midsystolic notching on echocardiogram. Interestingly, the Opotowsky method had a superior receiver-operating characteristic curve for discrimination of PVR >3 Wood units compared with the Abbas method.…”
Section: Discussionmentioning
confidence: 99%